Glacial meltwater and sea ice meltwater in the Prydz Bay, Antarctica - Cai, PH; 蔡平河; Huang, YP; 黄奕普; Chen, M; 陈敏; Liu, GS; 刘广山; Qiu, YS; 邱雨生; Chen, XB; Jin, DQ; et al. (Science in China Series D, 2003)
Measurements of deltaD and salinity were carried out in the Prydz Bay during two Antarctic cruises, the 13th and the 14th Chinese National Antarctic Research expeditions (CHINARE). Mass balance calculations based on deltaD and salinity showed that during the 13th CHINARE cruise, percentages of glacial meltwater and sea ice meltwater in the study region ranged from 0% to 3.82% and from -3.19% to 4.78%, respectively. Meanwhile, the percentages were 1.53%-3.98% and -3.80%-4.52% during the 14th CHINARE cruise. We depicted plots showing the horizontal distributions of glacial meltwater and sea ice meltwater, and found a footprint of Circumpolar Deep Water (CDW), which may suggest a strong upwelling in this regime. We also noticed a butterfly-like image in the plot, which resulted from two adjacent water masses. It is interesting to note that the butterfly-like image deflected anticlockwise with depth. We suggested that the cause of the deflection could be due to Ekman effect. Depth profiles of glacial meltwater within the Prydz Bay were fundamentally uniform, revealing that inflow of glacial meltwater to the basin was a slower process with respect to the vertical mixing in the water column. Nevertheless, percentage of sea ice meltwater decreased steadily with depth, presumably due to the effect of seasonal cycle of sea ice production.